STUDENTS’ ABILITY IN WRITING APPLICATION LETTER AT FOURTH SEMESTER ASM PERSADA BUNDA PEKANBARU - LIA DIANA (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2019)
ABSTRACT The study purposed to determine if application letter can improve the students writing skill. The research intent onto the students’ ability English functional writing, especially in writing application letter at the fourth semester ASM Persada Bunda Pekanbaru. The research participants were the fourth semester students of Akademi Sekretaris dan Manajemen (ASM) Persada Bunda Pekanbaru. There were 5 students. The research determined that application letter coud improve the students writing’s skill. This research is qualitative research. The writer collects the data using the test and the documentation. The test is written test of application letter in English subject for the students at the fourth semester of ASM Persada Bunda Pekanbaru. Then, the students’ sheet were corrected by scoring rubric of business letter. Finally, the writer analyzes the students’ score . Key words: Application letter, Writing Ability,